A Synergy of the Thousand Islands Tourism Office with Pokdarwis (Tourism Awareness Group) in the Development of Sustainable Tourism in Pramuka Island, Thousand Islands Regency - Budiarto (Eduturisma, 2020)
Pramuka Island is one of the marine tourism destinations that develops in the Thousand Islands Administrative District of DKI Jakarta. This study aimed to analyze the government’s synergy between Thousand Islands Regency Tourism and Culture Office and the Pramuka Island Tourism Awareness Group in developing sustainable tourism. This research is a qualitative descriptive study. Data collection are from observations, interviews, and documentation. The selection of informants used the purposive sampling technique. Data analysis techniques used the data triangulation model. This study indicated that synergy had been established in two phases, namely synergy in the planning phase of tourism development and in the phase of implementing work programs. However, not all work programs can be realized, where there are work programs that do not work in the synergy between the two because they are bumped into a higher policy, dealing with the policy of the Provincial Government of DKI Jakarta